Integrating Human Resource Development and Halal Tourism Strategies for Sustainable Development in Indonesia - Yoshinta, Dian; Suhariadi, Fendy; WIJOYO, SUPARTO (Technium Social Sciences Journal, 2024)
This research aims to explore the integration of human resource development (HRD) into the growth of the halal tourism industry in Indonesia. Using a literature review method, the study examines strategies to enhance the sector’s sustainable competitive advantage by focusing on HRD initiatives, including employee training, cultural competence, and service quality improvement in accordance with sharia principles. The findings indicate that while Indonesia has great potential in halal tourism, several barriers such as institutional readiness, inadequate infrastructure, and regulatory gaps hinder its full development. The study emphasizes the importance of continuous innovation, strategic marketing, and regulatory alignment to overcome these challenges. Recommendations include investing in human capital and fostering innovation to ensure Indonesia’s positioning as a global leader in halal tourism.